Early onset Arboleda-Tham syndrome due to KAT6A variants: Case report - Chen, Hongbo; Yu, Dan; Liu, Shanling; Xie, Hanbing; Qiao, Lina; Liu, Hanmin; Li, Weiran (Frontiers in Genetics, 2025)
BackgroundArboleda-Tham syndrome (ARTHS), caused by likely pathogenic or pathogenic variants in the KAT6A gene, is characterized by developmental delay, distinctive facial dysmorphic features, and congenital cardiac anomalies. ARTHS warrants consideration in the differential diagnosis of neonates exhibiting unexplained cardiac arrhythmias, seizures, and dysmorphic features, although neonatal-onset manifestations remain underrecognized.CaseWe report two Chinese patients with KAT6A variants diagnosed in the neonatal period who presented with life-threatening manifestations. Two unrelated neonates presented with severe cardiac arrhythmias or seizures within the first month of life, in association with congenital heart defects and developmental delay. Whole-exome sequencing (WES) identified two de novo KAT6A variants: a novel splice-site variant (c.3352 + 1G>C) in patient 1, who developed supraventricular tachycardia at 23 days of life, and a previously reported missense variant (c.4645G>A; p. Gly1549Ser) in patient 2 with seizures onset at 11 days. Both patients exhibited complex congenital heart disease (Patient 1: VSD, ASD and PDA; Patient 2: PFO and PDA), developmental delay, and characteristic dysmorphic features consistent with ARTHS.ConclusionThis report highlights the critical role of genomic sequencing in the diagnostic evaluation of neonates with unexplained cardiac arrhythmias or seizures. WES should be considered in neonates exhibiting severe early-onset multisystem involvement and dysmorphic features to investigate potential KAT6A variants. These findings substantially expand the phenotypic spectrum of ARTHS by documenting severe neonatal manifestations and contribute to a deeper understanding of KAT6A-related phenotypic variability.